European collaboration on relative effectiveness assessments: What is needed to be successful?. Issue 5 (May 2015) - Kleijnen, Sarah; Toenders, Wil; de Groot, Folkert; Huic, Mirjana; George, Elisabeth; Wieseler, Beate; Pavlovic, Mira; Bucsics, Anna; Siviero, Paolo D.; van der Graaff, Martin; Rdzany, Rafał; Kristensen, Finn Børlum; et al.
Highlights: We investigated barriers and success factors for European collaboration in the field of relative effectiveness assessments. Potential barriers identified relate to methodology, resources and challenges with national implementation (e.g. legal restrictions). Success factors for cross-border assessments are competent partners, quality and timely availability. National implementation of cross-border assessments is especially likely in countries with highest efficiency/quality gains. Further adaptation of the process and methods is required for optimal collaboration. Abstract: Objective: The objective of this study is to identify the possible barriers and critical success factors for the implementation of European collaboration in the field of relative effectiveness assessment (REA) of drugs. Methods: Data were gathered through semi-structured interviews with representatives from eight European health technology assessment (HTA) organisations involved in assessment of drugs for coverage decision-making (AAZ, AIFA, AHTAPol, HAS, HVB, IQWIG, NICE and ZiN). Results: Potential barriers identified mainly relate to methodology, resources and challenges with implementation in the respective national processes (e.g. legal restrictions). The most critical success factors for production of cross-border assessments were the continuous cooperation of competent partners, and the quality and timely availability of the assessment. Conclusion: Further adaptation of the process and methods is required for optimal collaboration. In the near future it can be expected that cross-border assessments will meet in particular the needs of smaller/middle-sized European countries and also European countries with less developed HTA systems as the potential efficiency/quality gains are the highest for these countries. Therefore, national implementation of cross-border assessments is especially likely in these countries in the coming years. Once more experience is gained with cross-border assessments, and successes become more evident, efficiency/quality gains may also be likely for some larger countries with well established processes.